Greater Acute Concussion Symptoms Are Associated With Longer Recovery Times in Adolescents. (December 2022) - Cook, Nathan E.; Gaudet, Charles E.; Maxwell, Bruce; Zafonte, Ross; Berkner, Paul D.; Iverson, Grant L.
We examined the association between the severity of acute concussion symptoms and time to return to school and to sports in adolescent student athletes. We hypothesized that there would be an association between the severity of acute symptoms experienced in the first 72 hours and functional recovery such that adolescents with the lowest burden of acute symptoms would have the fastest return to school and sports and those with the highest burden of symptoms would have the slowest return to school and sports. This injury surveillance cohort included 375 adolescent student athletes aged 14-19 years who sustained a sport-related concussion between 2014 and 2020. Athletic trainers documented time to return to school and to sports. A greater proportion of adolescents with the highest acute symptoms remained out of school at 3 (odds ratio [OR] = 2.5, 95% confidence interval [CI] 1.5-4.4), 5 (OR = 2.4, 95% CI 1.4-4.0), 7 (OR = 2.6, 95% CI 1.5-4.3), and 10 days (OR = 2.3, 95% CI 1.3-3.9) compared to those with the lowest acute symptoms. Similarly, a greater proportion of athletes with the highest acute symptoms remained out of sports at 7 (OR = 3.5, 95% CI 1.5-8.1), 10 (OR = 3.1, 95% CI 1.8-5.6), 14 (OR = 1.8, 95% CI 1.1-3.0), and 21 days (OR = 1.9, 95% CI 1.0-3.6) compared to those with the lowest acute symptoms. This study underscores the adverse effect of high acute symptom burden following concussion on return to school and to sports among adolescent student athletes. Conversely, student athletes with a low burden of acute symptoms have a faster return to school and to sports.